HISTOPATOLOGI ARTERI KORONARIA Rattus novergicus STRAIN WISTAR JANTAN SETELAH PEMBERIAN DIET ATEROGENIK SELAMA 5 MINGGU - Annisa Ul Hasanah; Enikarmila Asni; Zulkifli Malik (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2015)
ABSTRACTAtherosclerosis is a complex chronic disease characterized by the accumulation of lipid, trombosits, neutrophils, monocytes, and macrophages within arterial walls. Atherosclerosis could be induced in animal model ( Rattus novergicus ) by feeding atherogenic diet. The goal of this research was to analyze histopathological of coronary artery on male Rattus novergicus strain wistar after fed atherogenic diet for 5 weeks. This research was an experimental laboratory research with post test only with control design. Twelve male rats were segregated into two groups ( n=6 ) labelled as control fed standart and atherogenic group fed atherogenic diet containing cholic acid 0,2%, fat 5%, egg yolk 2% and induction with vitamin D3. After 5 weeks coronary artery was taken and histological slides were made and colored with Hematoxylin Eosin. The measured parameter were atherosclerosis lession score. The result showed 66% sampels that given standart diet and 100% sampels that given atherogenic diet showed atherosclerosis lession.The statistical test result showed there is no significant difference between control group and atherogenic group. ( p=0,328 ). The conclusion, atherosclerosis occurred in 4 sampels ( 66% ) of control group and 6 sampels ( 100% ) of atherogenic group. There was no significant difference in coronary artery histopathology Rattus novergicus between the control group with atherogenic group.Keywords : Atherosclerosis, atherogenic diet, coronary artery.